2012
DOI: 10.1666/11040.1
|View full text |Cite
|
Sign up to set email alerts
|

Within- and among-genus components of size evolution during mass extinction, recovery, and background intervals: a case study of Late Permian through Late Triassic foraminifera

Abstract: One of the best-recognized patterns in the evolution of organismal size is the tendency for mean and maximum size within a clade to decrease following a major extinction event and to increase during the subsequent recovery interval. Because larger organisms are typically thought to be at higher extinction risk than their smaller relatives, it has commonly been assumed that size reduction mostly reflects the selective extinction of larger species. However, to our knowledge the relative importance of within- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 98 publications
(119 reference statements)
7
44
0
Order By: Relevance
“…This approach has the potential to reduce the influence of juvenile or incomplete specimens and has been employed in previous body size studies (e.g., Rego et al, 2012;Zhang and Payne, 2012;Payne et al, 2013). We tested whether or not the size frequency distribution in each of the three environments followed the normal distribution using the Shapiro-Wilk test and found that none satisfied the test (nearshore: W=0.9784, p<0.0001; offshore: W=0.993, p=0.0496; basin: W=0.9845, p=0.0208) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has the potential to reduce the influence of juvenile or incomplete specimens and has been employed in previous body size studies (e.g., Rego et al, 2012;Zhang and Payne, 2012;Payne et al, 2013). We tested whether or not the size frequency distribution in each of the three environments followed the normal distribution using the Shapiro-Wilk test and found that none satisfied the test (nearshore: W=0.9784, p<0.0001; offshore: W=0.993, p=0.0496; basin: W=0.9845, p=0.0208) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, because proloculus size ranges over about eight orders of magnitude within each order, our measurement error is small relative to the overall distribution of proloculus sizes used in the analyses and will not affect any of our conclusions. Similarly, size variation within foraminiferan species is small relative to size variation among species (Rego et al ) and so the uncertainty introduced by using a single specimen to approximate a species will be small at the scale of the present analysis, which includes species spanning eight orders of magnitude in biovolume. Importantly, the proportional error in size measurements should not vary significantly with proloculus or test size because images of specimens are magnified to approximately the same size in the Ellis and Messina catalog.…”
Section: Methodsmentioning
confidence: 99%
“…Although the scope of this catalogue (>40,000 records) prohibits comprehensive taxonomic standardization, size trends in data designated as from the Superfamily Fusulinoidea in Ellis and Messina corresponded well with trends in a taxonomically and stratigraphically standardized North American dataset (Payne et al 2012). Analyses of size variation among specimens within species and species maxima within genera for Triassic foraminifera from south China show that the great majority of size variation is among species and genera rather than within them (Rego et al 2012). Comparison of monograph illustrations and bulk samples for bivalves and brachiopods shows that monographed specimens correlate with but are typically larger than the median or mean size of the bulk population (Krause et al 2007).…”
Section: Methodsmentioning
confidence: 99%